2018
DOI: 10.29089/2017.17.00026
|View full text |Cite
|
Sign up to set email alerts
|

Association between the effects of body mass index on lung volumes among students in Jiangsu Province

Abstract: I n t r o d u c t i o n : Obesity has been reported to develop lung problems and causes a significant medical health problem for the future of student's health. M a t e r i a l a n d m e t h o d s : This is a cross-sectional study among 255 581 students aged 7-22 years-old. Electronic spirometer device was used for diagnose of lung conditions, and ultrasonic scale machine (SY133) was used to measures body weight and height. BMI was calculated based on Chines Working Group on Obesity in China (WGOC) standard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…And the incidence of bad vital capacity weight index in normal weight, underweight, overweight and obese groups was 15.66, 5.15, 37.47, and 66.35%, respectively. These results indicated that the abnormal weight status was a strong risk factor for high BP and bad vital capacity weight index, which was generally in agreement with the previous results [31] , where a study covered Jiangsu province (North, South, Central) with approximately 255,581 244 students aged (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) years, in urban and rural regions. And this suggested that the prevalence of high BP and bad vital capacity weight index in less developed regions was comparable with the prevalence of these parameters in highly developed regions.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…And the incidence of bad vital capacity weight index in normal weight, underweight, overweight and obese groups was 15.66, 5.15, 37.47, and 66.35%, respectively. These results indicated that the abnormal weight status was a strong risk factor for high BP and bad vital capacity weight index, which was generally in agreement with the previous results [31] , where a study covered Jiangsu province (North, South, Central) with approximately 255,581 244 students aged (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) years, in urban and rural regions. And this suggested that the prevalence of high BP and bad vital capacity weight index in less developed regions was comparable with the prevalence of these parameters in highly developed regions.…”
Section: Discussionsupporting
confidence: 82%
“…In China, the prevalence of hypertension was 17.7% in 2002 and it was estimated that the direct economic burden reached 31.89 billion RMB [7] . Adult hypertension and the adverse effects of elevated BP on vascular structure and function may start very early in life [8] .…”
mentioning
confidence: 99%
“…Other studies have traced the correlation between lung volumes and dynamometry scores. A significantly low, moderately positive association of lung volume in young men and BMI was reported [5]. In other studies, no direct correlation was detected [6].…”
Section: Variability Of Anthropometric and Physiometric Indicators Of Young Menmentioning
confidence: 85%